Factors associated with hiv infection among sexually transmitted infection- clinic attendees in Kelantan, 2016- 2022 - Aminuddin, Abdul Mukmin M. (2023)
Background: The changing landscape of Human immunodeficiency virus (HIV) infection shifting from drug abuse to sexual contact as the primary of HIV transmission brought about new challenges in combating the spread of HIV worldwide and Malaysia is no exception. In response, Malaysia initiated state- based sexual health clinics in 2016 to reach out to those at risk, which was found to be effective in delivering HIV services that include early detection and prevention of HIV transmission among high-risk individuals as well as providing treatment for HIV positive patients. For Kelantan state, the Sexually Transmitted Infection (STI) clinics as they are known, was first established in Klinik Kesihatan Bandar Kota Bharu in 2016 expanded to include all the 10 districts 3 years later. Objective: This study aimed to determine the proportion of HIV positivity and factors influencing HIV infection among patients with STI who attended STI clinics in Kelantan from 2016 to 2022. Methodology: This study utilized a cross-sectional design whereby data were collected by extracting information from the records of patients who visited STI clinics in Kota Bharu, Pasir Puteh and Tumpat from the year 2016 to 2022. Logistic regression analyses and model were performed to identify factors related to HIV positivity among patients who attended STI clinics in Kelantan. Results: Out of 247 patients who attended the STI clinics involved in the study, 228 cases (93.3%) had documented HIV test results, of which 75 cases (32.9%) were HIV-positive. Significant factors associated with HIV infection among STI patients included age ≥30 years (AOR: 1.857, 95% CI 1.010, 3.416, p<0.046), male gender (AOR: 5.807, 95% CI 1.324, 25.466, p=0.020), divorced status (AOR: 9.407, 95% CI 1.074, 82.398, p= 0.043), working in private sector (AOR: 3.844, 95% CI 1.744, 8.473, p=0.001), and had syphilis (AOR: 6.612, 95% CI: 3.567, 12.259, p<0.001). Conclusion: About one third of the respondents were HIV positive and based on the final model, were associated with 3 factors- male gender, divorced and confirm STI diagnosis of syphilis. Strategies needed to prevent HIV positivity among the STI clinic attendees should address and focus on these 3 factors first.